Clinical Distribution and Resistance Profile of Pseudomonas aeruginosa Iso-lated from Patients in Al-Diwaniyah Province - Alaa Hassan Jabbar; Masar Riyadh Rashid Al-Mousawi; Ali Jalil Ali Alyassery (Karbala Journal of Medicine, 2025)
Background: Pseudomonas aeruginosa is a highly opportunistic pathogen known for its resistance to multiple antibiotics, posing significant challenges in clinical settings, particularly in nosocomial infections. Its resistance patterns will vary geographically, necessitating localized studies to guide effective treatment strategies. The study aimed to identify the distribution and resistance profile of P. aeruginosa in Al-Diwaniyah Province, Iraq. Methods: A cross-sectional survey was conducted in two hospitals from November 2024 to May 2025. Clinical specimens (burn exudate, wound swabs, and urine) were collected and analyzed using culture, biochemical tests, and the VITEK-2 system. Antimicrobial susceptibility testing was performed via disk diffusion and MIC determination. Statistical analysis was performed using SPSS. Results: From 240 patients included in this study, there were only 43 isolates of P. aeruginosa. The high infection rates occurred in males (62.8%) aged 17–32 years. Burn isolates exhibited the highest resistance, with 72.4% extensively drug-resistant (XDR) strains, while urinary tract infections (UTIs) were predominantly multidrug-resistant (MDR; 66.7%). Carbapenem resistance was alarmingly high (imipenem: 93.1% in burns and meropenem: 86.2%). UTIs were strongly associated with prior antibiotic use (100%), whereas burn and wound infections often occurred without antibiotic exposure (62% and 60%, respectively). Conclusions: P. aeruginosa in Al-Diwaniyah Province shows significant resistance, particularly in burns and among young adults. The findings underscore the need for stringent infection control measures, antibiotic stewardship, and alternative therapies to combat rising resistance. Future research should explore novel treatments like phage therapy to improve patient outcomes.